The Bible on television. - Bond, Helen K.; Adams, Edward (London [England] : Bloomsbury Publishing Ltd, 2020)
This volume examines and discusses selected Bible documentaries and academically informed dramatizations of the Bible. The major focus is UK mainline television, and on recent productions (mostly within the past 15 years) but there is also engagement with productions from the USA. After a critical introduction by the editors, charting and reflecting on the use of the Bible on television in recent years, the book falls into three sections. In the first section, a number of influential filmmakers and producers, including Ray Bruce and Jean-Claude Bragard, discuss their work in relation to the context and constraints of television (especially religious television) programming. The second section contains reflections of various academics who have acted as 'talking heads', historical consultants and presenters. They discuss different aspects of the process, including the extent to which they had influence and how their contributions were used. In the third section, a number of scholars assess the finished products, discussing what they tell us about the modern reception of the Bible. There is also consideration of how these productions influence biblical scholars and contribute to the scholarly agenda.
Preface Contents -- Contributors Introduction: Helen Bond, University of Edinburgh, UK and Edward Adams, King's College London, UK 1. Genesis of the Bible Documentary: the Development of Religious Broadcasting in the UK - Richard Wallis, University of Bournemouth, UK 2. The Bible According to TV - Jean-Claude Bragard, Television Producer 3. A Critical Black Christian Body: Resistance in in the Bible Documentary - Robert Beckford, Canterbury Christ Church University, UK 4. Interview with Ray Bruce - Television Producer, Edward Adams, King's College London, UK, and Helen Bond, University of Edinburgh, UK 5. The Story of Lumo - David Batty, Director, The Gospel of John 6. Scholars Working in Television: Some Personal Reflections and Advice - Joan Taylor, King's College London, UK 7. The Nativity on TV - Helen K. Bond, University of Edinburgh, UK 8. Putting Paul on TV: The Case of David Suchet: In The Footsteps of Saint Paul' - Edward Adams, King's College London, UK 9. Plundering Egypt: Exodus Documentaries and the Exploitation of History - Mark Harris, University of Edinburgh, UK 10. The History Channel's The Bible: an Epic...? - Meg Ramey, Messiah College, USA 11. 'When the Resurrected Biblical Epic Transferred to the Small Screen...and Promptly Died Again: A Critical Autopsy of the 2016 ABC Series of Kings and Prophets' - David Tollerton, University of Exeter, UK 12. How do 'Bible-users' respond to the Bible on TV? - Cheryl Hunt, University of Exeter, UK Index.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Bible -- Study and teaching; Television in religion; Television broadcasting -- Religious aspects -- Christianity; Mass media in religion; Biblical studies & exegesis; Electronic books